ANALISIS PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN KONSUMEN (Survei pada Konsumen TFP Kopi Warung Surakarta) - Zahra Audi Al Farel; Rahayu Triastity; Sumaryanto Sumaryanto (Universitas Slamet Riyadi, 2020)
This research was used to analyze the effect of service quality, product quality, and price on customer satisfaction of TFP Kopi Warung Surakarta. The population sample used is a TFP Kopi Warung Surakarta customers. The sample used in this research is 100 people respondents. The sampling technique use Purposive Sampling. The data analysis technique used is descriptive analysis techniques, multiple linear regression, t test, F test, and coefficient of determination.The result of the research shows that the persial and simultaneous service quality, product quality, and price positive and significant impact on customer satisfaction